2015
DOI: 10.3319/tao.2014.11.10.01(hy)
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Non-Point Source Pollution and Korean Green Factor

Abstract: In determining the relationship between the rational event mean concentration (REMC) which is a volume-weighted mean of event mean concentrations (EMCs) as a non-point source (NPS) pollution indicator and the green factor (GF) as a low impact development (LID) land use planning indicator, we constructed at runoff database containing 1483 rainfall events collected from 107 different experimental catchments from 19 references in Korea. The collected data showed that EMCs were not correlated with storm factors wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recent studies have established the impact of NPS pollutants in water environments. Lee et al [21] observed that NPS contaminants constituted 69.3% of the total pollution loads discharged from 4 major watersheds in Korea in 2010. Hu and Huang [22] monitored NPS from an agricultural watershed in southern China.…”
Section: Non-point Source Pollutionmentioning
confidence: 99%
“…Recent studies have established the impact of NPS pollutants in water environments. Lee et al [21] observed that NPS contaminants constituted 69.3% of the total pollution loads discharged from 4 major watersheds in Korea in 2010. Hu and Huang [22] monitored NPS from an agricultural watershed in southern China.…”
Section: Non-point Source Pollutionmentioning
confidence: 99%